Features of Carbon Regulation in the Republic of Belarus and the Russian Federation: Comparative Analysis and Trends - V. A. Liubchyk; V. E. Pinaev; V. N. Ukhova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article reviews international acts in the field of combating climate change (United Nations Framework Convention on Climate Change, Kyoto Protocol and Paris Agreement), identifies the main trends in the field of carbon regulation: emissions quoting; implementation of climate projects; introduction of greenhouse gas reporting and expansion of the legislative framework. A comparative analysis of the national legislation in force in the Republic of Belarus and the Russian Federation is carried out, its conditional classification is considered with the allocation of carbon regulation instruments being applied, viz. the market ones, the restrictive ones, the supporting ones and the auxiliary ones. The regulation of greenhouse gas emissions should include a wide range of activities and cannot be reduced solely to restrictive instruments. Market instruments include the national emissions trading system, international voluntary markets and instruments of international cooperation, while restrictive instruments include the introduction of carbon taxes, quotas, and mandatory carbon reporting. Among the examples of supporting instruments subsidies, targeted financing and tax preferences, as well as information policy may be noted. Auxiliary instruments include methodologies for quantitative assessment of greenhouse gas emissions and uptake, carbon reporting standards and tools for verification of reporting on greenhouse gas emissions, legislated possibility of implementing climate projects. The normative national regulation regarding the accounting of greenhouse gas emissions is considered, the categories of emission sources and greenhouse gases whose emissions are subject to accounting are identified. It is important to note that the legislation on greenhouse gases in the Republic of Belarus and the Russian Federation, as well as around the world, has not been finalized and is in the process of formation.